Tissue Engineering of Muscles and Cartilages Using Polyelectrolyte Hydrogels - Hyuck Joon Kwon (Advances in Materials Science and Engineering)
The prevalent nature of osteoarthritis that causes the erosion of joint surfaces and loss of mobility and muscle dystrophy that weakens the musculoskeletal system and hampers locomotion underlies the importance of developing functional replacement or regeneration of muscle and cartilage tissues. Polyelectrolyte gels have high potential as cellular scaffolds due to characteristic properties similar to biological matrixes. A number of in vitro and in vivo studies demonstrated that polyelectrolyte gels are useful for replacement and regeneration of muscle and cartilage tissues. In addition, it was also found that polyelectrolyte gels have high biocompatibility, durability, and resistance to biodegradation. Moreover, polyelectrolyte gels can overcome their drawbacks of mechanical behavior by introducing double network into the gel. This paper reviews the current status and recent progress of polyelectrolyte gel-based tissue engineering for repairs of muscle and cartilage tissues.